5-ALA ameliorates hepatic steatosis through AMPK signaling pathway. (August 2017) - Yu, Haoyong; Zhang, Mingliang; Ma, Yunqin; Lu, Junxi; Pan, Jiemin; Pan, Pan; Chen, Haibing; Jia, Weiping
Abstract : 5-Aminolevulinic acid (5-ALA), the first compound in the porphyrin synthesis pathway, has been reported to ameliorate the diabetic state in Otsuka Long-Evans Tokushima Fatty rats by reducing fat pad weight in the retroperitoneal region. Dietary supplementation with 5-ALA has additionally demonstrated the capacity to lower blood glucose and HbA1c levels among subjects with diabetes. The etiology of nonalcoholic fatty liver disease (NAFLD) is complex and its typical characteristics include obesity and insulin resistance. As 5-ALA supplementation has previously normalized glucose and insulin resistance, we sought to investigate whether 5-ALA had potential therapeutic effects on NAFLD and elucidate the signal pathway mediating these effects. To explore these questions, we fed C57BL/6J mice a high-fat diet (HFD) to induce a fatty liver disease and supplemented the diet-induced obese (DIO) mice with 5-ALA. The mice in the presence of 5-ALA demonstrated a decrease in body weight and hepatic lipid content and moderate improvement in glucose homeostasis compared to untreated controls. Further, we found that 5-ALA activated AMPK signaling pathway, which was correlated with enhanced lipolysis and fatty acid β-oxidation. Human hepatocarcinoma cells (HepG2 cells) treated with 5-ALA were additionally used to investigate the mechanics of 5-ALA. Treated cells had a higher expression of lipolysis-related genes, including PGC-1α. Our data indicated that 5-ALA might represent a novel compound that could be useful for the treatment of nonalcoholic fatty liver disease (NAFLD), likely through the restoration of phosphorylation levels of AMPK (Thr172) and acetyl-CoA (ACC) (Ser79), further enhanced PGC1α and CPT1α expression.